Cyclosporine A modulates CD103+ DC responses to fungal PAMPs - Liddicoat, Alex (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2022)
Cyclosporine A (CsA) is an immunosuppressant that protects against inflammatory diseases and graft rejection. Despite its strong efficacy, one side-effect of CsA is an increased risk of fungal infection. To minimise this, further research is required to determine the mechanisms by which CsA impacts on innate immune cell subsets that mediate antifungal immunity. Using both in vivo and in vitro models, this work examined the impact of CsA on migratory CD103+ DCs and type I IFNs, both emerging mediators of antifungal immunity. During intranasal challenge with fungal Zymosan, a clinically-available oral CsA formulation inhibited CD103+ DC trafficking to the lung-draining lymph nodes. In an in vitro CD103+ DC culture model, CsA inhibited Zymosan-induced migration and reduced the expression of the chemokine receptor CCR7, as well as co-stimulatory molecules. Intriguingly, CsA also inhibited CD103+ DC secretion of type I IFNs and IFNAR signalling in vitro, which was important for maturation and expression of CCR7, as well as migration of activated CD103+ DCs to the lung-draining lymph nodes in the in vivo model. These data suggest that CsA inhibits type I IFN-dependent activation and migration of CD103+ DCs, providing further insight into how the drug increases susceptibility to fungal infection.
APPROVED
Keywords: Cyclosporine A; CD103+ Dendritic cell; Fungi